Protection of human rights of asylum seekers and illegal migrants: Practice of European court of human rights - Đukanović Anđela (Međunarodni Problemi)
The European Court of Human Rights plays an important role in protecting the rights of asylum seekers and illegal migrants through a set of different human rights. Requests for interim measures under Rule 39 of the Rules of Court have also great importance. In cases involving illegal migrants and asylum-seekers, the Court was often in a difficult position, given the contradictions that could arise from the protection of human rights and the legitimate aim of the Contracting States to control the entry, residence and expulsion of aliens. The recent Courts judgments in the case of M. S. S. against Belgium and in the case of Jama Hirsi and others v. Italy are particularly important because of their remarkable influence on the perception of the common asylum system in the EU. [Projekat Ministarstva nauke Republike Srbije, br. 179029: Srbija u savremenim međunarodnim odnosima: Strateški pravci razvoja i učvršćivanja položaja Srbije u međunarodnim integrativnim procesima - spoljnopolitički, međunarodni ekonomski, pravni i bezbednosni aspekti]